Ethylene oxychlorination catalyst and preparation method thereof, and method for preparing 1, 2-dichloroethane through ethylene oxychlorination
By using ethylene oxychlorination catalysts supported by copper elements with γ-Al2O3 and Y-type molecular sieve composite support, the high equipment requirements and safety risks under pressurized conditions in the prior art were solved, and efficient hydrogen chloride conversion and 1,2-dichloroethane selectivity under normal pressure were achieved.
Patent Information
- Application Number
- CN202510561219.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-08-05
- Estimated Expiration
- 2045-04-29
AI Technical Summary
The existing ethylene oxychlorination catalysts require pressurization conditions to achieve high hydrogen chloride conversion and high 1,2-dichloroethane selectivity, which poses high equipment requirements and safety risks, and traditional catalysts are prone to produce by-products at high temperatures.
The composite support of γ-Al2O3 and Y-type molecular sieve is used to support copper elements and additive elements to form an ethylene oxychlorination catalyst, and the efficient oxychlorination reaction is achieved under normal pressure by improving the catalyst structure.
Under normal pressure, the hydrogen chloride conversion rate reaches more than 99%, and the selectivity of 1,2-dichloroethane reaches more than 98%, reducing equipment requirements and safety risks, and improving reaction efficiency and selectivity.
Smart Images

Figure CN120421025A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to an ethylene oxychlorination catalyst and a preparation method thereof, and a method for preparing 1,2-dichloroethane by ethylene oxychlorination. Background Art
[0002] Ethylene oxychlorination is one of the main processes for producing 1,2-dichloroethane (EDC), an important intermediate in the production of polyvinyl chloride (PVC). As demand for PVC increases, so does the demand for EDC, an intermediate used in the production of PVC. The key to improving the efficiency of EDC production lies in increasing the conversion rate of hydrogen chloride and the selectivity of EDC during the EDC production process. Developing more efficient catalysts has promising applications for improving hydrogen chloride conversion and EDC selectivity. Traditional catalysts are prone to producing byproducts at high temperatures, leading to resource waste and environmental pollution. However, by improving catalyst structure and materials, the generation of byproducts can be reduced, the selectivity of the target product can be increased, and environmental and energy-saving requirements can be met.
[0003] Prior art ethylene oxychlorination catalysts require pressurized conditions to achieve high hydrogen chloride conversion and high EDC selectivity. However, pressurized conditions place high demands on equipment and pose certain safety risks. Therefore, developing an ethylene oxychlorination catalyst that can achieve high hydrogen chloride conversion and high EDC selectivity at atmospheric pressure has significant economic value and application prospects for the chemical industry. Summary of the Invention
[0004] In view of this, the present invention aims to provide an ethylene oxychlorination catalyst and a preparation method thereof, as well as a method for preparing 1,2-dichloroethane by ethylene oxychlorination. The ethylene oxychlorination catalyst provided by the present invention can achieve ethylene oxychlorination at normal pressure with high hydrogen chloride conversion and high selectivity for 1,2-dichloroethane.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an ethylene oxychlorination catalyst, comprising a composite carrier and an active component attached to the composite carrier; the composite carrier is formed by γ-Al2O3 and Y-type molecular sieve; the active component comprises copper element; and the loading amount of the copper element is 3-6wt%.
[0007] Preferably, the active ingredient further comprises auxiliary elements, and the auxiliary elements include one or more of magnesium, cerium, calcium, potassium and lanthanum, and the loading amount of the auxiliary elements is 0.5 to 2 wt%.
[0008] Preferably, the mass ratio of the γ-Al2O3 and the Y-type molecular sieve is 1 to 2:1.
[0009] Preferably, the Y-type molecular sieve is a mesoporous Y-type molecular sieve or a microporous Y-type molecular sieve.
[0010] The present invention also provides a method for preparing the ethylene oxychlorination catalyst described in the above technical solution, comprising the following steps:
[0011] Mixing γ-Al2O3, Y-type molecular sieve and water, and sequentially performing a first impregnation, a first drying and a first calcination to obtain a composite support;
[0012] The composite support and the copper salt solution are mixed, and a first impregnation, a second drying and a second calcination are performed in sequence to obtain the ethylene oxychlorination catalyst.
[0013] Preferably, the mixing of γ-Al2O3, Y-type molecular sieve and water includes stirring mixing and ultrasonic mixing in sequence, and the time of the ultrasonic mixing is 20 to 40 minutes; the time of the first impregnation is 10 to 15 hours; the temperature of the first drying is 100 to 130°C; the temperature of the first calcination is 500 to 600°C, the holding time is 4 to 6 hours, and the atmosphere is air.
[0014] Preferably, the copper salt in the copper salt solution includes copper nitrate and / or copper chloride; and the mass ratio of the composite support to the copper salt solution is 1:0.03 to 0.06, calculated on the basis of copper element.
[0015] Preferably, the mixing of the composite carrier and the copper salt solution includes stirring mixing and ultrasonic mixing in sequence, and the ultrasonic mixing time is 20 to 40 minutes; the second impregnation time is 10 to 15 hours; the second drying temperature is 100 to 130°C, and the time is 10 to 15 hours; the second calcination temperature is 500 to 600°C, the insulation time is 6 to 12 hours, and the atmosphere is air.
[0016] The present invention also provides a method for preparing 1,2-dichloroethane by ethylene oxychlorination, comprising the following steps:
[0017] Using ethylene, hydrogen chloride and oxygen as raw materials, an oxychlorination reaction is carried out in the presence of a catalyst to obtain 1,2-dichloroethane;
[0018] The pressure of the oxychlorination reaction is 0.1 MPa;
[0019] The catalyst is the ethylene oxychlorination catalyst described in the above technical solution or the ethylene oxychlorination catalyst prepared by the preparation method described in the above technical solution.
[0020] Preferably, the flow ratio of ethylene, hydrogen chloride and oxygen is 1.05-1.1:2:0.6-0.7, and the total flow of ethylene, hydrogen chloride and oxygen is 35-38 mL / min, and the gas space velocity is 200-250 h / min in terms of hydrogen chloride. -1 ;
[0021] The temperature of the oxychlorination reaction is 190-230°C;
[0022] The oxychlorination reaction is carried out in a reactor, which includes a fixed bed reactor or a fluidized bed reactor.
[0023] The present invention provides an ethylene oxychlorination catalyst.
[0024] The present invention utilizes a composite support of γ-Al2O3 and Y-type molecular sieve, replacing a single support. This composite support possesses a high specific surface area, a rich pore structure, and numerous active sites. The composite support exhibits a unique pore structure, adjustable acidity and alkalinity, and excellent thermal stability, making it resistant to carbon deposit formation. The unique pore structure of the composite support allows for a more uniform distribution of active components, reducing agglomeration of active ingredients, enhancing their effective utilization, and maintaining high reaction activity. The ethylene oxychlorination catalyst of the present invention utilizes a composite support of γ-Al2O3 and Y-type molecular sieve, combined with copper as the active component. This catalyst is capable of ethylene oxychlorination even at atmospheric pressure, achieving high hydrogen chloride conversion and high selectivity for 1,2-dichloroethane. Experimental data demonstrate that the catalyst achieves over 99% hydrogen chloride conversion and over 98% selectivity for 1,2-dichloroethane when used in ethylene oxychlorination reactions.
[0025] Furthermore, the addition of auxiliary elements can increase the dispersion of active components, slow down the deactivation process of active sites by changing the acid-base properties of the catalyst surface, and improve the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A flow chart for preparing the ethylene oxychlorination catalyst provided by the present invention;
[0027] Figure 2 A flow chart of the device for evaluating the catalyst of the present invention;
[0028] Figure 3 This is the EDS graph of the Cu5-Y molecular sieve / γ-Al2O3 composite support catalyst obtained in Example 3. DETAILED DESCRIPTION
[0029] The present invention provides an ethylene oxychlorination catalyst, comprising a composite carrier and an active component attached to the composite carrier; the composite carrier is formed by γ-Al2O3 and Y-type molecular sieve; the active component comprises copper element; and the loading amount of the copper element is 3-6wt%.
[0030] The ethylene oxychlorination catalyst provided by the present invention includes a composite support, which is formed by γ-Al2O3 and Y-type molecular sieve. In the present invention, the mass ratio of the γ-Al2O3 and the Y-type molecular sieve is preferably 1 to 2:1, specifically preferably 1:1, 1.5:1 or 2:1. In the present invention, the Y-type molecular sieve is preferably a mesoporous Y-type molecular sieve or a microporous Y-type molecular sieve, and is further preferably a mesoporous Y-type molecular sieve. Compared with β molecular sieve, the content of non-framework aluminum in Y-type molecular sieve is lower. Therefore, during the preparation process of the ethylene oxychlorination catalyst, the Y-type molecular sieve is easier to maintain a good pore structure and acidity distribution, reducing the risk of deactivation. At the same time, in order to improve the activity of the ethylene oxychlorination catalyst, the composite support formed by the combination of Y-type molecular sieve and γ-Al2O3 has a unique pore structure, adjustable acidity and alkalinity and excellent thermal stability, which can effectively delay the accumulation of carbon deposits, thereby improving the activity and stability of the ethylene oxychlorination catalyst and extending the service life of the ethylene oxychlorination catalyst. The composite carrier enables the conversion rate of hydrogen chloride to reach over 99% and the selectivity of 1,2-dichloroethane to reach over 98%.
[0031] The ethylene oxychlorination catalyst provided by the present invention includes an active ingredient attached to a composite support, wherein the active ingredient includes copper; the copper loading is 3 to 6 wt%, and more preferably 3 wt%, 4 wt%, 5 wt%, or 6 wt%. In the present invention, the copper loading refers to the percentage of the mass of the copper to the mass of the support.
[0032] In the present invention, the active ingredient preferably also includes an auxiliary element, and the auxiliary element preferably includes one or more of magnesium, cerium, calcium, potassium and lanthanum, and is further preferably lanthanum. In the present invention, the loading amount of the auxiliary element is preferably 0.5 to 2wt%, specifically preferably 0.5wt%, 1wt%, 1.5wt% or 2wt%. In the present invention, the loading amount of the auxiliary element refers to the percentage of the mass of the auxiliary element to the mass of the carrier. The addition of auxiliary elements can increase the dispersion of the active components, slow down the deactivation process of the active sites by changing the acid-base properties of the catalyst surface, and improve the stability of the catalyst.
[0033] Single supports are widely used in research on ethylene oxychlorination, but their low catalytic activity limits the conversion rate of the oxychlorination reaction. The present invention forms an ethylene oxychlorination catalyst by combining a Y-type molecular sieve with γ-Al2O3 and loading it with copper as the active component. This ethylene oxychlorination catalyst significantly enhances its catalytic capacity and service life, exhibiting high catalytic activity. This ethylene oxychlorination catalyst exhibits excellent catalytic performance, improving HCl conversion and EDC selectivity.
[0034] The present invention also provides a method for preparing the ethylene oxychlorination catalyst described in the above technical solution, comprising the following steps:
[0035] Mixing γ-Al2O3, Y-type molecular sieve and water, and sequentially performing a first impregnation, a first drying and a first calcination to obtain a composite support;
[0036] The composite support and the copper salt solution are mixed, and second impregnation, second drying and second calcination are performed in sequence to obtain the ethylene oxychlorination catalyst.
[0037] Figure 1 The preparation flow chart of the ethylene oxychlorination catalyst provided by the present invention is shown below in conjunction with Figure 1 The preparation method of the present invention is described.
[0038] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0039] The present invention mixes gamma-Al2O3, Y-type molecular sieve and water, and sequentially performs first impregnation, first drying and first calcination to obtain a composite carrier.
[0040] In the present invention, the γ-Al2O3 is preferably powdered γ-Al2O3. In a specific embodiment of the present invention, the specific surface area of the γ-Al2O3 is preferably 144m 2 / g.
[0041] In the present invention, the Y-type molecular sieve is preferably a mesoporous Y-type molecular sieve or a microporous Y-type molecular sieve, and is further preferably a mesoporous Y-type molecular sieve. In the present invention, the Y-type molecular sieve is preferably a powdered Y-type molecular sieve. In a specific embodiment of the present invention, the specific surface area of the Y-type molecular sieve is preferably 310m 2 / g.
[0042] In the present invention, the mass ratio of the γ-Al2O3 and the Y-type molecular sieve is preferably 1 to 2:1, specifically preferably 1:1, 1.5:1 or 2:1.
[0043] In the present invention, the mass ratio of the total mass of the γ-Al2O3 and Y-type molecular sieve to water is preferably 10g:25-35mL, specifically preferably 10g:25mL, 10g:30mL or 10g:35mL.
[0044] In the present invention, the mixing of γ-Al2O3, Y-type molecular sieve and water preferably includes stirring and ultrasonic mixing (referred to as the first ultrasonic mixing) in sequence; the time of the first ultrasonic mixing is preferably 20 to 40 minutes, specifically preferably 20 minutes, 30 minutes or 40 minutes. In the present invention, the temperature of the first impregnation is preferably room temperature, that is, no additional heating or cooling is required; the time of the first impregnation is preferably 10 to 15 hours, specifically preferably 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.
[0045] In the present invention, the temperature of the first drying is preferably 100-130°C, specifically preferably 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, and the time of the first drying is preferably 10-15 hours, specifically preferably 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours. In the present invention, the first drying is preferably carried out in a blast drying oven.
[0046] After the first drying and before the first calcination, the present invention preferably further comprises a first grinding. The present invention does not impose any specific restrictions on the parameters of the first grinding, as long as the bulk material obtained by the first drying can be ground into powder.
[0047] In the present invention, the temperature of the first calcination is preferably 500-600°C, specifically preferably 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C or 600°C, the holding time is preferably 4-6h, specifically preferably 4h, 5h or 6h, and the atmosphere is preferably air.
[0048] In the present invention, γ-Al2O3, Y-type molecular sieve and water are mixed, and a first impregnation, a first drying and a first calcination are carried out in sequence, so that a full composite of γ-Al2O3 and Y-type molecular sieve can be achieved; in particular, the first calcination can also form more abundant acid sites, promote the subsequent loading of metals or other components, and improve the catalytic performance.
[0049] After obtaining the composite support, the present invention mixes the composite support with a copper salt solution, and sequentially performs a second impregnation, a second drying, and a second calcination to obtain the ethylene oxychlorination catalyst.
[0050] In the present invention, the copper salt in the copper salt solution preferably includes copper nitrate and / or copper chloride, more preferably copper nitrate, and more preferably copper nitrate trihydrate (Cu(NO3)2·3H2O).
[0051] In the present invention, the mass ratio of the composite support to the copper salt solution is preferably 1:0.03 to 0.06, specifically preferably 1:0.03, 1:0.04, 1:0.05 or 1:0.06, calculated as copper element.
[0052] In the present invention, the solvent of the copper salt solution is preferably water, more preferably deionized water. In the present invention, the concentration of the copper salt solution is preferably 10 to 20 mg / mL, specifically preferably 10 mg / mL, 13.3 mg / mL, 16.7 mg / mL or 20 mg / mL, calculated as elemental copper.
[0053] In the present invention, the usage ratio of the copper salt solution and the composite carrier is preferably 30 mL:9-11 g, specifically preferably 30 mL:9 g, 30 mL:10 g or 30 mL:11 g.
[0054] In the present invention, when the active ingredient of the ethylene oxychlorination catalyst preferably includes an auxiliary element, the composite support is preferably immersed in a copper salt solution containing an auxiliary salt. In the copper salt solution containing the auxiliary salt, the mass ratio of the auxiliary element to the composite support is preferably 0.005 to 0.02:1, specifically preferably 0.005:1, 0.01:1, 0.015:1, or 0.02:1. In the present invention, when the auxiliary element is lanthanum, the auxiliary salt is preferably lanthanum nitrate, more preferably lanthanum nitrate hexahydrate (La(NO3)3·6H2O). In the present invention, the usage ratio of the copper salt solution containing the auxiliary salt to the composite support is preferably 30 mL:9 to 11 g, specifically preferably 30 mL:9 g, 30 mL:10 g, or 30 mL:11 g.
[0055] In the present invention, the mixing of the composite carrier and the copper salt solution preferably includes stirring mixing and ultrasonic mixing (referred to as the second ultrasonic mixing) in sequence, and the time of the second ultrasonic mixing is preferably 20 to 40 minutes, specifically preferably 20 minutes, 30 minutes or 40 minutes.
[0056] In the present invention, the temperature of the second impregnation is preferably room temperature, that is, no additional heating or cooling is required; the time is preferably 10 to 15 hours, specifically preferably 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.
[0057] In the present invention, the second drying temperature is preferably 100-130°C, specifically preferably 100°C, 110°C, 120°C or 130°C; the second drying time is preferably 10-15 hours, specifically preferably 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours. In the present invention, the second drying is preferably carried out in a blast drying oven.
[0058] After the second drying and before the second calcination, the present invention preferably further comprises a second grinding. The present invention does not specifically limit the parameters of the second grinding, as long as the bulk material obtained by the second drying can be ground into powder.
[0059] In the present invention, the temperature of the second calcination is preferably 500-600°C, specifically preferably 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, or 600°C; the holding time is preferably 6-12 hours, specifically preferably 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, or 12 hours; and the atmosphere is preferably air. In the present invention, the second calcination can facilitate the decomposition of the metal salt into oxides during the calcination process, forming catalytically active metal oxide species.
[0060] In the present invention, the ethylene oxychlorination catalyst is preferably in powder form.
[0061] The present invention also provides a method for preparing 1,2-dichloroethane by ethylene oxychlorination, comprising the following steps:
[0062] Using ethylene, hydrogen chloride and oxygen as raw materials, an oxychlorination reaction is carried out in the presence of a catalyst to obtain 1,2-dichloroethane;
[0063] The pressure of the oxychlorination reaction is 0.1 MPa;
[0064] The catalyst is the ethylene oxychlorination catalyst described in the above technical solution or the ethylene oxychlorination catalyst prepared by the preparation method described in the above technical solution.
[0065] In the present invention, the ethylene oxychlorination catalyst is preferably pretreated before use, and the pretreatment preferably comprises: tableting the ethylene oxychlorination catalyst and then sieving it to 40-60 mesh.
[0066] In the present invention, the oxychlorination reaction is preferably carried out in a reactor, preferably a fixed bed reactor or a fluidized bed reactor. In the present invention, the fixed bed reactor preferably comprises a zirconium tube reactor, the catalyst is preferably located in the middle section of the zirconium tube reactor; and the upper and lower sections of the zirconium tube reactor are preferably filled with quartz sand.
[0067] Before the ethylene, hydrogen chloride and oxygen are introduced, the present invention preferably further comprises introducing a protective atmosphere into the reactor; the protective atmosphere preferably comprises nitrogen.
[0068] In the present invention, the flow ratio of ethylene, hydrogen chloride and oxygen is preferably 1.05-1.1:2:0.6-0.7, specifically preferably 1.05:2:0.65, and the total flow rate of ethylene, hydrogen chloride and oxygen is preferably 35-38 mL / min, specifically preferably 35 mL / min, 36 mL / min, 37 mL / min or 38 mL / min, calculated as hydrogen chloride, and the gas space velocity is preferably 200-250 h -1 , specifically preferably 200h -1 , 210h -1 , 220h -1 , 230h -1 , 240h -1 or 250h -1 In the present invention, the ethylene, hydrogen chloride, and oxygen preferably enter the control pipeline from a steel cylinder through a pressure reducing valve, and then enter the zirconium tube reactor after the flow rate is precisely controlled by a precision flow meter; the ethylene, hydrogen chloride, and oxygen enter the zirconium tube reactor from the bottom, are heated by the quartz sand located in the lower section of the zirconium tube reactor, and then fully contact with the catalyst in the middle section to carry out the oxychlorination reaction.
[0069] In the present invention, the pressure of the oxychlorination reaction is 0.1 MPa, that is, normal pressure.
[0070] In the present invention, the temperature of the oxychlorination reaction is preferably 190-230°C, specifically preferably 190°C, 200°C, 210°C, 220°C or 230°C.
[0071] In the present invention, after the oxychlorination reaction, the selectivity of the reaction product obtained is determined by gas chromatography. Simultaneously, the gas flowing out of the top of the zirconium tube reactor is introduced into water to absorb hydrogen chloride. The absorption liquid is titrated with a NaOH solution using an acid-base titration method to calculate the conversion rate of hydrogen chloride and evaluate the performance of the catalyst.
[0072] Figure 2 This is a flow chart of the catalyst evaluation apparatus of the present invention. Specifically, before the evaluation begins, nitrogen is introduced to create a nitrogen atmosphere in the reactor. Ethylene, hydrogen chloride, and oxygen are then introduced to carry out the oxychlorination reaction. During the oxychlorination reaction, the left valve is opened and the right valve is closed. The generated gas and liquid are passed into a product conical flask. The gas is then passed into water to remove HCl, and the purified gas is then collected into a gas bag. To measure the hydrogen chloride conversion, the left valve is closed and the right valve is opened. The gas is collected for 2 minutes, and the hydrogen chloride conversion is then measured.
[0073] The ethylene oxychlorination catalyst and its preparation method, and the method for preparing 1,2-dichloroethane by ethylene oxychlorination provided by the present invention are described in detail below with reference to the following examples. However, these examples should not be construed as limiting the scope of protection of the present invention.
[0074] Example 1
[0075] 5 g of Y-type mesoporous molecular sieve (specific surface area 310 m 2 / g) and 5gγ-Al2O3 (specific surface area 144m 2 / g) was added into 30 mL of deionized water and stirred to mix evenly, followed by ultrasonic mixing for 30 min, and then immersed at room temperature for 12 h, placed in a forced air drying oven at 110° C. for 12 h, and the dried material was ground into powder; and then calcined in an air atmosphere at 560° C. for 4 h to obtain a Y molecular sieve / γ-Al2O3 composite support.
[0076] The specific surface area and pore size of the Y molecular sieve / γ-Al2O3 composite carrier were tested by BET method. The results showed that the specific surface area was 170m 2 / g, pore size is 11nm.
[0077] 1.1325 g of Cu(NO3)2·3H2O was uniformly dispersed in 30 mL of deionized water to obtain a copper salt solution; then 10 g of Y molecular sieve / γ-Al2O3 composite carrier was added to the copper salt solution and stirred to mix evenly, followed by ultrasonic mixing for 30 min, and then immersed at room temperature for 12 h, placed in a forced air drying oven at 110°C for 12 h, and the dried material was ground into powder; then calcined in an air atmosphere at 560°C for 4 h to obtain a Cu3-Y molecular sieve / γ-Al2O3 composite carrier catalyst, wherein the copper element loading amount was 3 wt%.
[0078] Catalyst evaluation: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. Nitrogen was first introduced to place the reactor in a nitrogen atmosphere. Then ethylene, hydrogen chloride and oxygen were introduced. The total flow rate of ethylene, hydrogen chloride and oxygen was controlled at 37 mL / min, with a flow ratio of 1.05:2:0.65. The gas space velocity calculated as hydrogen chloride was 220 h / min. -1 The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 hours of operation are shown in Tables 1 and 2.
[0079] Example 2
[0080] 5 g of Y-type mesoporous molecular sieve (specific surface area 310 m 2 / g) and 5gγ-Al2O3 (specific surface area 144m 2 / g) was added into 30 mL of deionized water and stirred to mix evenly, followed by ultrasonic mixing for 30 min; then, it was immersed at room temperature for 12 h, placed in a forced air drying oven at 110° C. for 12 h, and the dried material was ground into powder; and then calcined in an air atmosphere at 560° C. for 4 h to obtain a Y molecular sieve / γ-Al2O3 composite support.
[0081] 1.51 g of Cu(NO3)2·3H2O was uniformly dispersed in 30 mL of deionized water to obtain a copper salt solution; 10 g of a Y molecular sieve / γ-Al2O3 composite carrier was then added to the copper salt solution and stirred to mix evenly, followed by ultrasonic mixing for 30 min, followed by immersion at room temperature for 12 h, drying in a forced air drying oven at 110°C for 12 h, and grinding the dried material into powder; and calcining in an air atmosphere at 560°C for 4 h to obtain a Cu4-Y molecular sieve / γ-Al2O3 composite carrier catalyst, wherein the copper element loading amount was 4 wt%.
[0082] Catalyst evaluation: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. Nitrogen was first introduced to place the reactor in a nitrogen atmosphere. Then ethylene, hydrogen chloride and oxygen were introduced. The total flow rate of ethylene, hydrogen chloride and oxygen was controlled at 37 mL / min, with a flow ratio of 1.05:2:0.65. The gas space velocity calculated as hydrogen chloride was 220 h / min. -1 The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 hours of operation are shown in Tables 1 and 2.
[0083] Example 3
[0084] 5 g of Y-type mesoporous molecular sieve (specific surface area 310 m 2 / g) and 5gγ-Al2O3 (specific surface area 144m 2 / g) was added into 30 mL of deionized water and stirred to mix evenly, followed by ultrasonic mixing for 30 min, and then immersed at room temperature for 12 h, placed in a forced air drying oven at 110° C. for 12 h, and the dried material was ground into powder; and then calcined in an air atmosphere at 560° C. for 4 h to obtain a Y molecular sieve / γ-Al2O3 composite support.
[0085] 1.8875 g of Cu(NO3)2·3H2O was uniformly dispersed in 30 mL of deionized water to obtain a copper salt solution; then 10 g of Y molecular sieve / γ-Al2O3 composite carrier was added to the copper salt solution and stirred to mix evenly, followed by ultrasonication for 30 min, and then immersed for 12 h at room temperature, placed in a forced air drying oven at 110°C for 12 h, and the dried material was ground into powder; then calcined in an air atmosphere at 560°C for 4 h to obtain a Cu5-Y molecular sieve / γ-Al2O3 composite carrier catalyst, wherein the copper element loading amount was 5 wt%.
[0086] The EDS pattern of the obtained Cu5-Y molecular sieve / γ-Al2O3 composite support catalyst is shown in Figure 3 As shown, from Figure 3 It can be seen that the catalyst surface is distributed with signals of various elements, including Cu, Al, Si, and O, which are distributed on the catalyst surface in blue, green, yellow, and red, respectively. This indicates that the copper element is evenly dispersed on the surface of the composite support, forming a Cu5-Y molecular sieve / γ-Al2O3 composite support catalyst.
[0087] Catalyst evaluation: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. Nitrogen was first introduced to place the reactor in a nitrogen atmosphere. Then ethylene, hydrogen chloride and oxygen were introduced. The total flow rate of ethylene, hydrogen chloride and oxygen was controlled at 37 mL / min, with a flow ratio of 1.05:2:0.65. The gas space velocity calculated as hydrogen chloride was 220 h / min. -1 The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 hours of operation are shown in Tables 1 and 2.
[0088] Example 4
[0089] 5 g of Y-type mesoporous molecular sieve (specific surface area 310 m 2 / g) and 5gγ-Al2O3 (specific surface area 144m 2 / g) was added into 30 mL of deionized water and stirred to mix evenly, followed by ultrasonic mixing for 30 min, and then immersed at room temperature for 12 h, placed in a forced air drying oven at 110° C. for 12 h, and the dried material was ground into powder; and then calcined in an air atmosphere at 560° C. for 4 h to obtain a Y molecular sieve / γ-Al2O3 composite support.
[0090] 2.265 g of Cu(NO3)2·3H2O was evenly dispersed in 30 mL of deionized water and stirred to obtain a copper salt solution; then 10 g of Y molecular sieve / γ-Al2O3 composite carrier was added to the copper salt solution and stirred to obtain a copper salt solution, followed by ultrasonic mixing for 30 min, followed by immersion at room temperature for 12 h, drying in a forced air drying oven at 110°C for 12 h, and grinding the dried material into powder; and then calcining in an air atmosphere at 560°C for 4 h to obtain a Cu6-Y molecular sieve / γ-Al2O3 composite carrier catalyst, wherein the copper element loading amount was 6 wt%.
[0091] Catalyst evaluation: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. Nitrogen was first introduced to place the reactor in a nitrogen atmosphere. Then ethylene, hydrogen chloride and oxygen were introduced. The total flow rate of ethylene, hydrogen chloride and oxygen was controlled at 37 mL / min, with a flow ratio of 1.05:2:0.65. The gas space velocity calculated as hydrogen chloride was 220 h / min. -1 The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 hours of operation are shown in Tables 1 and 2.
[0092] Table 1 Effect of Cu loading on HCl conversion and EDC selectivity (reaction 7h)
[0093]
[0094] Table 2 Effect of Cu loading on HCl conversion and EDC selectivity (reaction time 800 h)
[0095]
[0096] Example 5
[0097] 5 g of Y-type mesoporous molecular sieve (specific surface area 310 m 2 / g) and 5gγ-Al2O3 (specific surface area 144m 2 / g) was added into 30 mL of deionized water and stirred to mix evenly, followed by ultrasonic mixing for 30 min, and then immersed at room temperature for 12 h, placed in a forced air drying oven at 110° C. for 12 h, and the dried material was ground into powder; and then calcined in an air atmosphere at 560° C. for 4 h to obtain a Y molecular sieve / γ-Al2O3 composite support.
[0098] 1.8875g Cu(NO3)2·3H2O and 0.156g La(NO3)3·6H2O were uniformly dispersed in 30mL deionized water to obtain a salt solution; then 10g Y molecular sieve / γ-Al2O3 composite carrier was added to the above salt solution, stirred and mixed evenly, ultrasonically mixed for 30min, then immersed at room temperature for 12h, placed in a blast drying oven at 110℃ for 12h, and the dried material was ground into powder; then calcined in air atmosphere at 560℃ for 4h to obtain La 0.5 Cu5-Y molecular sieve / γ-Al2O3 composite carrier catalyst, wherein the loading amount of copper element is 5wt% and the loading amount of lanthanum element is 0.5wt%.
[0099] Catalyst evaluation: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. Nitrogen was first introduced to place the reactor in a nitrogen atmosphere. Then ethylene, hydrogen chloride and oxygen were introduced. The total flow rate of ethylene, hydrogen chloride and oxygen was controlled at 37 mL / min, with a flow ratio of 1.05:2:0.65. The gas space velocity calculated as hydrogen chloride was 220 h / min. -1 The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 hours of operation are shown in Tables 3 and 4.
[0100] Example 6
[0101] 5 g of Y-type mesoporous molecular sieve (specific surface area 310 m 2 / g) and 5gγ-Al2O3 (specific surface area 144m 2 / g) was added into 30 mL of deionized water and stirred to mix evenly, followed by ultrasonic mixing for 30 min, and then immersed at room temperature for 12 h, placed in a forced air drying oven at 110° C. for 12 h, and the dried material was ground into powder; and then calcined in an air atmosphere at 560° C. for 4 h to obtain a Y molecular sieve / γ-Al2O3 composite support.
[0102] 1.8875g Cu(NO3)2·3H2O and 0.312g La(NO3)3·6H2O were uniformly dispersed in 30mL deionized water to obtain a salt solution; then 10g Y molecular sieve / γ-Al2O3 composite carrier was added to the above salt solution and stirred to mix evenly, then ultrasonicated for 30min, then immersed for 12h at room temperature, placed in a blast drying oven at 110℃ for 12h, and the dried material was ground into powder; then calcined in an air atmosphere at 560℃ for 4h to obtain a La1Cu5-Y molecular sieve / γ-Al2O3 composite carrier catalyst, wherein the loading amount of copper element is 5wt% and the loading amount of lanthanum element is 1wt%.
[0103] Catalyst evaluation: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. Nitrogen was first introduced to place the reactor in a nitrogen atmosphere. Then ethylene, hydrogen chloride and oxygen were introduced. The total flow rate of ethylene, hydrogen chloride and oxygen was controlled at 37 mL / min, with a flow ratio of 1.05:2:0.65. The gas space velocity calculated as hydrogen chloride was 220 h / min. -1 The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 hours of operation are shown in Tables 3 and 4.
[0104] Example 7
[0105] 5 g of Y-type mesoporous molecular sieve (specific surface area 310 m 2 / g) and 5gγ-Al2O3 (specific surface area 144m 2 / g) was added into 30 mL of deionized water and stirred to mix evenly, followed by ultrasonic mixing for 30 min; then, it was immersed at room temperature for 12 h, placed in a forced air drying oven at 110° C. for 12 h, and the dried material was ground into powder; and then calcined in an air atmosphere at 560° C. for 4 h to obtain a Y molecular sieve / γ-Al2O3 composite support.
[0106] 1.8875g Cu(NO3)2·3H2O and 0.468g La(NO3)3·6H2O were uniformly dispersed in 30mL deionized water to obtain a copper salt solution; 10g Y molecular sieve / γ-Al2O3 composite carrier was then added to the above salt solution and stirred to mix evenly, and then ultrasonically mixed for 30min, and then immersed at room temperature for 12h, placed in a blast drying oven at 110℃ for 12h, and the dried material was ground into powder; and then calcined in an air atmosphere at 560℃ for 4h to obtain La1.5 Cu5-Y molecular sieve / γ-Al2O3 composite carrier catalyst, wherein the loading amount of copper element is 5wt% and the loading amount of lanthanum element is 1.5wt%.
[0107] Catalyst evaluation 1: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. Nitrogen was first introduced to place the reactor in a nitrogen atmosphere. Then ethylene, hydrogen chloride, and oxygen were introduced. The total flow rate of ethylene, hydrogen chloride, and oxygen was controlled at 37 mL / min, with a flow ratio of 1.05:2:0.65. The gas space velocity based on hydrogen chloride was 220 h / min. -1 The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 hours of operation are shown in Tables 3 and 4.
[0108] Example 8
[0109] 5 g of Y-type mesoporous molecular sieve (specific surface area 310 m 2 / g) and 5gγ-Al2O3 (specific surface area 144m 2 / g) was added into 30 mL of deionized water, mixed and stirred evenly, then ultrasonicated and immersed at room temperature for 12 h, placed in a forced air drying oven at 110° C. for 12 h, and calcined in an air atmosphere at 560° C. for 4 h to obtain a Y molecular sieve / γ-Al2O3 composite support.
[0110] 1.8875g Cu(NO3)2·3H2O and 0.623g La(NO3)3·6H2O were evenly dispersed in 30mL deionized water, and then 10g Y molecular sieve / γ-Al2O3 composite support was added and mixed and stirred evenly, ultrasonicated and impregnated at room temperature for 12h, placed in a forced air drying oven at 110°C for 12h, and calcined in an air atmosphere at 560°C for 4h to obtain a La2Cu5-Y molecular sieve / γ-Al2O3 composite support catalyst, wherein the loading amount of copper element is 5wt% and the loading amount of lanthanum element is 2wt%.
[0111] Catalyst evaluation: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. Nitrogen was first introduced to place the reactor in a nitrogen atmosphere. Then ethylene, hydrogen chloride and oxygen were introduced. The total flow rate of ethylene, hydrogen chloride and oxygen was controlled at 37 mL / min, with a flow ratio of 1.05:2:0.65. The gas space velocity calculated as hydrogen chloride was 220 h / min. -1The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 hours of operation are shown in Tables 3 and 4.
[0112] Table 3 Effect of the amount of additive elements added on HCl conversion and EDC selectivity (reaction time 7 h)
[0113]
[0114] Table 4 Effect of the amount of additive elements added on HCl conversion and EDC selectivity (reaction time 800h)
[0115]
[0116] Comparative Example 1
[0117] 1.8875 g Cu(NO3)2·3H2O and 0.468 g La(NO3)3·6H2O were uniformly dispersed in 30 mL deionized water, and then 10 g γ-Al2O3 (with a specific surface area of 144 m 2 / g) were mixed and stirred evenly, ultrasonicated and immersed at room temperature for 12 hours, placed in a blast drying oven at 110 ° C for 12 hours, and calcined in an air atmosphere at 560 ° C for 4 hours to obtain La 1.5 Cu5 / γ-Al2O3 catalyst, wherein the loading amount of copper element is 5wt% and the loading amount of lanthanum element is 1.5wt%.
[0118] Catalyst evaluation: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. The total flow rate of C2H4, HCl and O2 was controlled at 37 mL / min, the flow ratio was 1.05:2:0.65, and the gas space velocity (GHV) was 220 h / min. -1 The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 h of operation are shown in Tables 5 and 6.
[0119] Comparative Example 2
[0120] 1.8875g Cu(NO3)2·3H2O and 0.468g La(NO3)3·6H2O were uniformly dispersed in 30mL deionized water, and then 10g Y-type mesoporous molecular sieve (specific surface area of 310m 2 / g) were mixed and stirred evenly, ultrasonicated and immersed at room temperature for 12 hours, placed in a blast drying oven at 110 ° C for 12 hours, and calcined in an air atmosphere at 560 ° C for 4 hours to obtain La 1.5 Cu5 / Y molecular sieve catalyst, wherein the loading amount of copper element is 5wt% and the loading amount of lanthanum element is 1.5wt%.
[0121] Catalyst evaluation: The prepared catalyst was pressed and sieved to 40-60 mesh. The pressed and sieved catalyst was loaded into a fixed bed reactor. The total flow rate of C2H4, HCl and O2 was controlled at 37 mL / min, the flow ratio was 1.05:2:0.65, and the gas space velocity (GHV) was 220 h / min. -1 The reaction temperature was 190-230°C and the pressure was 0.1 MPa. The EDC selectivity of the reaction products was determined by gas chromatography. The gas flowing out of the reactor was passed into water to absorb HCl. The absorption liquid was titrated with NaOH solution using an acid-base titration method to calculate the HCl conversion. Specific experimental data and results for 7 and 800 h of operation are shown in Tables 5 and 6.
[0122] Table 5 Effect of different carriers on HCl conversion and EDC selectivity (reaction 7h)
[0123]
[0124] Table 6 Effect of different carriers on HCl conversion and EDC selectivity (reaction time 800h)
[0125]
[0126] The ethylene oxychlorination catalyst of the present invention adopts γ-Al2O3 and Y-type molecular sieve as composite carriers, and optimizes the catalytic performance by loading copper elements and adding auxiliary elements. The catalyst has a high specific surface area, rich pore structure and excellent thermal stability, and can significantly improve the conversion rate of hydrogen chloride and the selectivity of EDC. It can be found through the examples that: with the continuous increase of copper loading, the activity of the Cu5-Y molecular sieve / γ-Al2O3 composite carrier catalyst is better, the conversion rate of hydrogen chloride reaches 99.31%, and the selectivity of EDC reaches 95.03%. However, too high copper loading may cause copper species to agglomerate, forming large particles of copper oxide, which cannot provide enough active sites, thereby affecting the catalytic effect. Therefore, the performance of the catalyst can be effectively improved by adding auxiliary elements to modify it, further improving the activity and selectivity of the catalyst, thereby improving the efficiency of the oxychlorination reaction. The addition of auxiliary elements can increase the dispersion of the active component copper element, slow down the deactivation process of the active sites, La 1.5 The Cu5-Y molecular sieve / γ-Al2O3 composite support catalyst has good activity, with the conversion rate of hydrogen chloride reaching 99.61% and the selectivity of EDC reaching 98.71%.
[0127] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. An ethylene oxychlorination catalyst, characterized in that The invention comprises a composite carrier and an active component attached to the composite carrier; the composite carrier is formed by γ-Al2O3 and Y-type molecular sieve; the active component comprises copper element; and the loading amount of the copper element is 3-6wt%.
2. The ethylene oxychlorination catalyst according to claim 1, characterized in that The active ingredient further includes auxiliary elements, which include one or more of magnesium, cerium, calcium, potassium and lanthanum. The loading amount of the auxiliary elements is 0.5 to 2 wt%.
3. The ethylene oxychlorination catalyst according to claim 1, wherein The mass ratio of the γ-Al2O3 and the Y-type molecular sieve is 1 to 2:
1.
4. The ethylene oxychlorination catalyst according to claim 1 or 3, characterized in that The Y-type molecular sieve is a mesoporous Y-type molecular sieve or a microporous Y-type molecular sieve.
5. The method for preparing the ethylene oxychlorination catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing γ-Al2O3, Y-type molecular sieve and water, and sequentially performing a first impregnation, a first drying and a first calcination to obtain a composite support; The composite support and the copper salt solution are mixed, and second impregnation, second drying and second calcination are performed in sequence to obtain the ethylene oxychlorination catalyst.
6. The preparation method according to claim 5, characterized in that The mixing of the γ-Al2O3, Y-type molecular sieve and water includes stirring mixing and ultrasonic mixing in sequence, wherein the ultrasonic mixing time is 20 to 40 minutes; the first impregnation time is 10 to 15 hours; the first drying temperature is 100 to 130°C; the first calcination temperature is 500 to 600°C, the holding time is 4 to 6 hours, and the atmosphere is air.
7. The preparation method according to claim 5, characterized in that The copper salt in the copper salt solution includes copper nitrate and / or copper chloride; calculated on the basis of copper element, the mass ratio of the composite carrier to the copper salt solution is 1:0.03-0.
06.
8. The preparation method according to claim 5 or 7, characterized in that The mixing of the composite carrier and the copper salt solution includes stirring mixing and ultrasonic mixing in sequence, wherein the ultrasonic mixing time is 20 to 40 minutes; the second impregnation time is 10 to 15 hours; the second drying temperature is 100 to 130° C. and the time is 10 to 15 hours; the second calcination temperature is 500 to 600° C. and the insulation time is 6 to 12 hours, and the atmosphere is air.
9. A method for preparing 1,2-dichloroethane by ethylene oxychlorination, characterized in that: The following steps are involved: Using ethylene, hydrogen chloride and oxygen as raw materials, an oxychlorination reaction is carried out in the presence of a catalyst to obtain 1,2-dichloroethane; The pressure of the oxychlorination reaction is 0.1 MPa; The catalyst is the ethylene oxychlorination catalyst according to any one of claims 1 to 4 or the ethylene oxychlorination catalyst prepared by the preparation method according to any one of claims 5 to 8.
10. The method according to claim 9, characterized in that The flow ratio of ethylene, hydrogen chloride and oxygen is 1.05-1.1:2:0.6-0.7, and the total flow of ethylene, hydrogen chloride and oxygen is 35-38 mL / min, calculated as hydrogen chloride, and the gas space velocity is 200-250 h -1 ; The temperature of the oxychlorination reaction is 190-230°C; The oxychlorination reaction is carried out in a reactor, which includes a fixed bed reactor or a fluidized bed reactor.
Citation Information
Patent Citations
Olefin oxychlorination catalyst, preparation method thereof and preparation method of dichloroethane
CN102463125A
Copper-based composite catalyst for ethylene oxychlorination reaction and preparation method thereof
CN117696121A
Catalyst carrier, ethylene oxychlorination catalyst, and preparation methods and applications of catalyst carrier and ethylene oxychlorination catalyst
CN118304877A
Composite carrier catalyst as well as preparation method and application thereof
CN118744010A
Composite catalyst, preparation method thereof and method for preparing cyclohexenyl cyclohexanone
CN119680628A
Cited By
Preparation method of catalyst for ethylene oxychlorination reaction
CN121732197A